How to motivate people for donor eyes with active support and participation of NGOs - Kakkanatt, Anthrayose; Anand, Anu F.; Gopinath, Geethu (International Journal of Research in Medical Sciences, 2018)
Background: Corneal diseases are among the major causes of vision loss and blindness in the world today, after cataract and glaucoma. In India, it is estimated that there are approximately 6.8 million people who have vision less than 6/60 in at least one eye due to corneal diseases. On an average, the country needs 200,000 corneas in a year, and only 44,806 are collected. Therefore, creating awareness amongst the masses and encouraging them to pledge their eyes for donation is critical. We utilized the help of local voluntary, social, and religious organizations for the implementation of the awareness and motivation program. Methods: Authors utilized the help of local voluntary, social, and religious organizations for the selection of sites, local publicity, arrangement and mobilization of people and other infrastructure. Schools, colleges, clubs, organizations, trade union offices, public functions, etc were utilized for the arrangement of this awareness and motivation camps. Results: As a result of the eye donation awareness and motivation programs we got 1035 eyes in the past 12 years. Starting with 24 eyes in the first year rising to 126eyes in the 12th year. 64% of the eyes received were utilized for keratoplasty and 36% were used for research purposes. Conclusions: Out experiences has convinced us the important role of social and religious organization and its leaders in spreading the message of eye donation among people. These organizations have an active role in creating awareness and motivation of eye donation to clear the backlog of corneal blindness in India.